The influence of Muhammad Haqqi Al-Nazilli (M. 1884) on the religious practices of the Malays [Pengaruh Muhammad Haqqi Al-Nazilli (M. 1884) terhadap amalan keagamaan masyarakat Melayu] - Abdullah W.H.; Hussien S.S.B.; Muhammad Mustaqim Mohd.Zarif (Kolej University Islam Sultan Azlan Shah, 2024)
Muhammad Haqqi al-Nazilli (d. 1884) was amongst the most important Muslim scholars in the nineteenth century. Despite his Turkish origin, he spent most of his life and career as a resident scholar in Mecca specializing in the fields of hadith and Sufism. Apart from teaching, he had also published a number of important religious works written in Arabic. His opus entitled Khazinah al-Asrar Jalilah al-Adhkar is of high importance and significance especially amongst his students from the Malay World. It is a work based on the Prophetic hadith concerning the benefits and virtues of the verses of the Quran as well as certain religious practices. However, not much is known or studied about him or his work. Therefore, this paper aims to shed some light on this matter. Apart from discussing his life and works from the historical perspective, main emphasis is given on analyzing his scheme of hadith appraisal from Khazinah al-Asrar and its influence on the Malays. The findings highlight his reconciliatory approach towards the hadith between the methods of the hadith scholars and that of the Sufis and its role in shaping the religious practices amongst the Muslims, particularly those from the Malay World.